4-Terminal Inorganic Perovskite/Organic Tandem Solar Cells Offer 22% Efficiency - Liu, Ling; Xiao, Hanrui; Jin, Ke; Xiao, Zuo; Du, Xiaoyan; Yan, Keyou; Hao, Feng; Bao, Qinye; Yi, Chenyi; Liu, Fangyang; Wang, Wentao; Zuo, Chuantian; et al. (Nano-Micro Letters, 2022)
After fast developing of single-junction perovskite solar cells and organic solar cells in the past 10 years, it is becoming harder and harder to improve their power conversion efficiencies. Tandem solar cells are receiving more and more attention because they have much higher theoretical efficiency than single-junction solar cells. Good device performance has been achieved for perovskite/silicon and perovskite/perovskite tandem solar cells, including 2-terminal and 4-terminal structures. However, very few studies have been done about 4-terminal inorganic perovskite/organic tandem solar cells. In this work, semi-transparent inorganic perovskite solar cells and organic solar cells are used to fabricate 4-terminal inorganic perovskite/organic tandem solar cells, achieving a power conversion efficiency of 21.25% for the tandem cells with spin-coated perovskite layer. By using drop-coating instead of spin-coating to make the inorganic perovskite films, 4-terminal tandem cells with an efficiency of 22.34% are made. The efficiency is higher than the reported 2-terminal and 4-terminal inorganic perovskite/organic tandem solar cells. In addition, equivalent 2-terminal tandem solar cells were fabricated by connecting the sub-cells in series. The stability of organic solar cells under continuous illumination is improved by using semi-transparent perovskite solar cells as filter. Highlights: 1 4-Terminal inorganic perovskite/organic tandem solar cells were made by using semi-transparent inorganic perovskite solar cells and narrow-bandgap organic solar cells as the sub-cells, yielding a power conversion efficiency of 22.34%, which is the highest efficiency for inorganic perovskite/organic tandem solar cells. 2 Inorganic perovskite solar cells made by drop-coating (self-spreading) gave much higher power conversion efficiency than the cells made by spin-coating, enabling perovskite/organic tandem solar cells with higher efficiency.